ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEMISKINAN DI PROVINSI JAWA BARAT DENGAN REGRESI LINIER BERGANDA - Umyana Umyana; Moh Yamin Darsyah (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
The government's efforts to tackle the problem of poverty are very serious. the central government in overcoming this poverty is to implement regional autonomy in which each local government has the right to regulate its own region in order to solve the problems that exist in the area of West Java. poverty is seen as an inability from the economic side to meet basic needs of food and not food measured in terms of public spending. Poor people are residents with average per capita expenditure per month below the poverty line. Analysis of the factors affecting poverty using secondary data, the data is obtained from the publication of Badan Pusan Statistik Provinsi Jawa Barat. Where the relationship linearly between two or more independent variables with dependent Poverty line (Y) is not influenced by other factors, the number of poor (X1), GDP (X2) education (X3). The results of this study using R test with multiple linear regression analysis method to determine the factors of poverty in the west. Can be seen p-valuenya the number of poor people p-value 0.615 then do not affect the poverty in the area of West Java, Gross Regional Domestic Product (PDRB) P-value 0.692 then no effect on poverty in West Java and Education P-value <2e-16 * ** so education affects poverty in the area of West Java. Keywords: Poverty, Multiple Linear Regression